Paleoethnobotany and Ancient Alcohol Production: A Mini-Review - Biwer, Matthew E; VanDerwarker, Amber M (Ethnobiology Letters, 2015)
The production and consumption of alcoholic beverages in the past is an important consideration when addressing issues involving ancient food. However, successfully demonstrating that alcoholic beverages were produced in prehistoric contexts is problematic. As a result, archaeobotanists have developed a multi-scalar approach, incorporating multiple lines of evidence, to argue for the production of fermented beverages in the past.